Research on the latest trends in Bangla named entity recognition - Farhan, Niloy; Joy, Saman Sarker; Mannan, Tafseer Binte (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.